Three-dimensional cooperative guidance laws with impact velocity and impact angles constraints - Li, Yajun; Zhu, Mingjia; An, Binghe; Zhi, Yongran; Liu, Lei; Fan, Huijin; Wang, Bo (Aerospace science and technology, 2025)
In this paper, we propose a cooperative guidance algorithm designed to enable multiple missiles to simultaneously attack a target at desired terminal angles while maintaining control over their impact velocities. The three-dimensional (3-D) guidance laws incorporate a guidance law along the line-of-sight (LOS) and additional guidance laws in the normal and lateral directions relative to the LOS. Initially, a nonlinear cooperative guidance law is developed along the LOS to achieve consensus in range-to-go for multiple missiles, ensuring that all missiles converge to a range-to-go of zero with the specified impact velocity. Additionally, by employing a fixed-time sliding manifold design with state index coefficients, the normal and lateral guidance laws ensure that the LOS angles converge to their desired values within a fixed time frame. The proposed guidance laws are robust, effectively suppressing system disturbances, such as unknown target acceleration treated as external disturbances. Finally, we validate the performance of the proposed guidance law in a 3-D guidance scenario through comprehensive simulation experiments. •Proposes a 3-D cooperative guidance law with fixed-time convergence for dynamic battle conditions.•Introduces relative velocity constraints for missile stability and adjustable impact velocity.•Uses range-to-go for coordination, improving accuracy and performance.